Keterkaitan antara Akuntansi Syariah dan Zakat dalam Manajemen Keuangan - Muammar Khaddafi; Siti Hadisa Fitri; Putri Handayani; Indah Nirwana Sari; Asmimi Basri; Balqis Humaira (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The main objective of this research is to analyse the extent of the application of sharia accounting in the management of zakat in zakat institutions. This research uses a qualitative approach with literature study as the main method. The qualitative approach was chosen because it allows to deeply explore abstract concepts such as Islamic accounting, zakat, and financial management, as well as their interconnections. Based on the findings of this study, it can be concluded that Islamic accounting has a crucial relationship and role in the management of zakat. The application of sharia principles such as al-amana, al-adl, and al-khas in zakat accounting not only ensures transparent and accountable fund management, but also increases public trust in zakat institutions. Good accounting practices such as segregation of funds, preparation of transparent financial statements, and independent audits are key in realising effective and efficient zakat management.